(untitled) (Revista de Medicina Clinica, 2025)
Introduction: This study evaluates the influence of sex on the clinical and epidemiological characteristics of patients participating in a contemporary Cardiac Rehabilitation Program (CRP). It examines the impact of new scientific recommendations and pharmacological treatment on lipid profiles. Patients and Methods: A prospective, single-center study was conducted on patients with ischemic heart disease enrolled in a CRP (2015–2020). Demographic, clinical, and lipid profile data were collected at four time points. The evolution of low-density lipoprotein cholesterol (LDL-C) was analyzed by sex, and temporal cohorts were compared pre- and post-implementation of the 2019 European guidelines for dyslipidemia management. Results: A total of 1,379 patients were included (83% male, mean age 61.5±11 years). The most prevalent cardiovascular risk factors were dyslipidemia (66.8%), hypertension (53.5%), diabetes mellitus (32.4%), and smoking (37.4%). LDL-C levels significantly decreased during the CRP, with lower baseline values in men than in women (66.4 mg/dL ±21.6 vs. 70.5 mg/dL ±23.2, p<0.01). At 6 months, LDL-C levels remained low (68.4 mg/dL±19.9 vs. 73.2 mg/dL±25.6). The 2019–2020 cohort showed a greater reduction in LDL-C (113.1 mg/dL±38.3 vs. 55.4 mg/dL±19.49) compared to the 2015–2019 cohort (116.5 mg/dL±40.5 vs. 70.49 mg/dL±21.5). The use of high-potency statins and ezetimibe increased, while PCSK9 inhibitors were used minimally. Tolerance to high-intensity statins was high. Conclusion: The CRP demonstrated lasting benefits in reducing LDL-C, achieving lower levels in men than in women, and optimized lipid-lowering treatment with an acceptable safety profile.